The Development of Digital-Based Teaching Materials to Improve Student Ability in Developing Economic Learning Tools - Thamrin, Thamrin (FKIP Universitas Lampung, 2023)
Education personnel institutions (LPTK) are suspected of not being able to produce competent teacher candidates. The teaching materials used are still conventional, therefore information and communication technology (ICT) in the learning process is necessary to apply through digital-based learning. This research aims to: (1). identify the learning needs of the economics learning planning course desired by students. (2). test the feasibility of the developed digital-based economic learning planning teaching materials (3). tested the effectiveness of using digital-based economic learning planning teaching materials which were developed to improve students' ability to develop economic learning tools. This study used research and development (R & D) methods. The population were 115 students consisting of classes A, B and C who were attending economic learning planning courses. The sample for this study were students in the third semester of the business education study program, which consisted of two classes A and B. Class A consisted of 40 students as an experimental class and class B as a control class consisting of 40 students. The sampling technique used a random sampling technique. Data collection was carried out by conducting formative evaluations and limited trials one by one after the learning process. The results of this study indicate that digital-based teaching materials are appropriate and effective for use in planning economic learning. The t-test at α 0.05 states that the learning outcomes of planning economic lessons taught using digital-based teaching materials are higher than the group of students who are taught without digital-based teaching materials.Keywords: Digital-based teaching materials, student ability, learning toolsDOI: http://dx.doi.org/10.23960/E3J/v6i1.1-7